EFEKTIVITAS PENERAPAN METODE KOOPERATIF TIPE SCRAMBLE PADA KETERAMPILAN MEMBACA DAN MENULIS AKSARA JAWA DI KELAS V SEKOLAH DASAR ISLAM TERPADU AL-HADI, JATEN, KARANGANYAR TAHUN AJARAN 2024/2025 - Handayani, Widiyantari Sri; Rochmawan, Alfian Eko; Fatchurrohman, Muhammad (Al’ulum Jurnal Pendidikan Islam, 2025)
This study aims to measure the effectiveness of the Cooperative Scramble method in Javanese script instruction for fifth-grade students at SDIT Al-Hadi Jaten. The research employs a comparative quantitative approach with statistical descriptions covering the mean, minimum, maximum, and standard deviation. Conducted at SDIT Al-Hadi, Jaten, Karanganyar, the study includes a population of 87 students and a sample of 47 students selected through cluster random sampling. Validity testing used Aiken’s formula, while reliability was assessed with the Sperman Brown formula, and data analysis employed descriptive statistics. Prerequisite tests included normality and homogeneity tests, and the hypothesis was examined using cooperative analysis techniques. Results indicate that students' reading and writing skills in Javanese script were relatively high before the method was applied (pre-test average of 52.87), improved after the method's application (post-test average of 67.6), with the method’s effectiveness demonstrated by a significance value of 0.141 in the homogeneity test.